Analysis of Human Resource Strengthening Programs through Decent Living Standards in the Human Development Index of Kediri City - EKA SILVIANA, OKTALIA; Kurniawati, Endah (Universitas Muhammadiyah Pontianak, 2026)
This study examines human resource strengthening programs based on decent living standards as a strategy to improve the Human Development Index (HDI) in Kediri City. The research aims to analyze program synergy, effectiveness, and sustainability in addressing poverty, unemployment, and skill mismatches. A descriptive qualitative method with a document study approach was employed, using official government reports and statistical data from 2019–2023, analyzed inductively through content analysis. The findings indicate that integrated programs have strengthened purchasing power, expanded employment opportunities, and enhanced workforce skills. These results imply the importance of cross-sectoral coordination and program integration to support sustainable human development.